PENERAPAN TEKNOLOGI PENGOLAHAN TELUR ITIK PADA KELOMPOK WANITA TANI TERNAK ITIK LIBURENG DI DESA LIBURENG KECAMATAN TANETE RIAJA KABUPATEN BARRU - Abustam, Effendi; Malaka, Ratmawati; Ali, Hikma M.; Johana C. Likadja, Hajrawati, Muh. Irfan Said,; Baco, Sudirman; Maruddin, Fatma; Murpiningrum, Farida Nur Yuliati, Endah (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. The application of processing technology on duck eggs by application of liquid smoke on duck salting and technology of egg shredded to woman duck farmer community is aimed to improve shelf life and quality of duck eggs by egg salting and egg shredded. This application technology was applied on duck farmer community with hoping to improve knowledge and know-how and also by indirect to improve the revenue of farmers community. This activity consist of training in theory and practical, making product post training, examination of product quality and monitoring and evaluation. The activity took place since August until December 2012. The results of activity showed that all participants were very enthusiast to receive the offering technology, and then they were making duck egg salting with liquid smoke product and egg shredded. The quality and quantity of duck egg salting with liquid smoke were better than egg salting without liquid smoke. The quality of egg shredded was very good with protein and fat content was 16.57% and 32.11% respectively. The result of evaluation showed that there are 2 business units which to be active in technology application concern of course materials during training.